2012
DOI: 10.1371/journal.pone.0053278
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Health Trajectories in the African American Health Cohort

Abstract: BackgroundSelf-rated health taps health holistically and dynamically blends prior health histories with current illness burdens and expectations for future health. While consistently found as an independent predictor of functional decline, sentinel health events, physician visits, hospital episodes, and mortality, much less is known about intra-individual changes in self-rated health across the life course, especially for African Americans.Materials/MethodsData on 998 African American men and women aged 50–64 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 46 publications
4
49
3
1
Order By: Relevance
“…Studies among adults indicate individuals with higher income, higher education, or who self-identify as White fare better in SRH. 57 These disparities may originate in adolescent development, but research has yet to explore this.…”
Section: Introductionmentioning
confidence: 99%
“…Studies among adults indicate individuals with higher income, higher education, or who self-identify as White fare better in SRH. 57 These disparities may originate in adolescent development, but research has yet to explore this.…”
Section: Introductionmentioning
confidence: 99%
“…SRH is a very efficient clinical measure of overall health (“Would you say your health is excellent, very good, good, fair, or poor?”) (Idler & Benyamini, 1997; Mossey & Shapiro, 1982). It also reflects the continuum of a person's perceived health by eliciting thoughts on previous, current, and future health (Ayyagari et al, 2012; Idler & Benyamini, 1997). Therefore, for individuals who have a rich history filled with unique experiences and circumstances, such as older African American adults, SRH may be a more appropriate indicator of holistic health than reports of the number/presence of health conditions or objective appraisals of physical health.…”
Section: Introductionmentioning
confidence: 99%
“…19–21 These health disparities are also reflected in self-rated health, with African Americans over the age of 50 rating themselves as having poorer health on average than their White counterparts. 22 Studies have indicated that a variety of characteristics, such as depressive symptoms, smoking, and less education, were associated with poorer self-rated health 23 and self-rated health trajectories 24 among African Americans. However, to our knowledge, no previous studies have examined the association of loneliness and self-rated health among African Americans of any age group.…”
mentioning
confidence: 99%